Hemicellulose-based hydrogels for advanced applications - Xu, Ying; Liu, Kun; Yang, Yanfan; Kim, Min-Seok; Lee, Chan-Ho; Zhang, Rui; Xu, Ting; Choi, Sun-Eun; Si, Chuanling (Frontiers in Bioengineering and Biotechnology, 2023)
Hemicellulose-based hydrogels are three-dimensional networked hydrophilic polymer with high water retention, good biocompatibility, and mechanical properties, which have attracted much attention in the field of soft materials. Herein, recent advances and developments in hemicellulose-based hydrogels were reviewed. The preparation method, formation mechanism and properties of hemicellulose-based hydrogels are introduced from the aspects of chemical cross-linking and physical cross-linking. The differences of different initiation systems such as light, enzymes, microwave radiation, and glow discharge electrolytic plasma are summarized. The advanced applications and developments of hemicellulose-based hydrogels in the fields of controlled drug release, wound dressings, high-efficiency adsorption, and sensors are summarized. Finally, the challenges faced in the field of hemicellulose-based hydrogels are summarized and prospected.